Third International Conference on Semantics, Knowledge and Grid (SKG 2007) 2007
DOI: 10.1109/skg.2007.32
|View full text |Cite
|
Sign up to set email alerts
|

Question Similarity Calculation for FAQ Answering

Abstract: Frequently Asked Question (FAQ) answering is a very useful module in automatic question answering (QA) systems where calculation of question similarity is a key problem. In this paper, we propose a new method for measuring the similarity between users' questions and the questions in a FAQ database. Both statistic measure and semantic information are employed. Statistic similarity is calculated based on dynamically formed vectors while semantic similarity is calculated by utilizing word similarity based onWordN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…In this paper, we focus on the FAQ answering task. Previous work on answering a question given FAQ pages (FAQ-Finder [8], Auto-FAQ [28], [2,11,13,21,23]) was based on traditional feature engineering for surfacing statistical/semantic similarities between query and questions. Most of these works considered similarity between query and questions, very few considered query-answer similarity.…”
Section: Related Workmentioning
confidence: 99%
“…In this paper, we focus on the FAQ answering task. Previous work on answering a question given FAQ pages (FAQ-Finder [8], Auto-FAQ [28], [2,11,13,21,23]) was based on traditional feature engineering for surfacing statistical/semantic similarities between query and questions. Most of these works considered similarity between query and questions, very few considered query-answer similarity.…”
Section: Related Workmentioning
confidence: 99%
“…Attribute Recognition: Once entities present in the user question are identified, questions stored in the attribute-tuples of the identified entity node are extracted. A similarity measure of the given question with each of the extracted questions [12] is computed as follows:…”
Section: Answer Retrieval (Anr) Modulementioning
confidence: 99%
“…One branch of work calculated the semantic similarity of questions based on Natural Language Processing (NLP). For example, Song et al [34] first identified keywords in questions, and then calculated semantic similarity between questions based on the keywords. They also extended the semantic similarity to statistic similarity, which was calculated using the cosine similarity between two question vectors.…”
Section: Question Similarity Calculationmentioning
confidence: 99%
“…In order to conduct a state-of-the-art machine learning prediction experiment, we survey existing studies for the features used in student performance prediction [22,24], mouse trajectory feature definition [33,42], and possible methods in question similarity calculation [1,4,34,36,37]. We summarize this knowledge with our dataset and task, then we propose our prediction framework in Figure 2.…”
Section: Overall Prediction Frameworkmentioning
confidence: 99%